Variant Branching Pattern of Axillary Artery: A Case Report - Swamy Ravindra Shantakumar; K. G. Mohandas Rao (Case Reports in Vascular Medicine)
During routine dissection of an approximately 50-year-old male cadaver for the undergraduate medical students at Melaka Manipal Medical College, Manipal University, Manipal, we came across a variation in branching pattern of right axillary artery. The second part of axillary artery gave rise to a common trunk which divided into the subscapular and lateral thoracic arteries. The third part of right axillary artery gave rise to anterior and posterior circumflex humeral arteries. Variations in the branching pattern of axillary artery are important for the surgeons performing interventional or diagnostic procedures in cardiovascular diseases.